Sistem Pendukung Keputusan Penerimaan Beasiswa Peningkatan Prestasi Akademik (PPA) Berbasis Web - Sariati, Sariati; Aprianti, Winda; Fathurrahmani, Fathurrahmani (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
Determination of the decision that recipient of Academic Achievement Improvement scholarships in the Informatics Engineering is still done conventionally by the student division at the institutional and study program level, namely by collecting files, inputting and calculating data in Microsoft Excel, and selecting based on the data calculation results. The large number of scholarship applicants results in the inefficiency of the scholarship admission process so that it needs a system that can support the decision to receive scholarships. The proposed web-based system uses the weighted product method in determining the ranking of scholarship applicants. The criteria used in the problem of determining the scholarship include the Grade Point Average (GPA), parents' income, and the number of dependents. The results of applying weighted products to sample data of scholarship applicants in the Informatics Engineering in 2017 provide ranking information for scholarship applicants where Student 3 gets first rank, which means getting the first priority as a recipient of scholarship. The system that was built has displayed the results of the application of weigted products and graphical displays that make it easier for users to obtain information about the registration of scholarships.